Design, synthesis and pharmacological evaluation of efficacy selective β2 adrenoceptor agonists - Lumb, Elliott (2019)
Asthma and chronic obstructive pulmonary disease both involve constriction or obstruction of the airways and are causes of morbidity and mortality worldwide. To treat these conditions, patients are often prescribed β2 adrenoceptor agonists (β2AR). Activation of the β2AR leads to smooth muscle relaxation within the respiratory tract, and therefore increased airflow throughout the lungs. The caveat of current approved drugs, is that due to structural similarities with the β2AR endogenous agonist adrenaline, these compounds can also activate the β1AR. Activation of the β1AR, increases heart rate and force of contraction. This becomes problematic when patients also suffer from heart disease (40% of COPD patients). There is therefore, a requirement for β2AR agonists with efficacy selectivity to the β2AR.